The Role of Digital Marketing in Improving Dodol Sales Performance - Agustina, Putri; Yafiz, Muhammad; Nasution, Muhammad Irwan Padli (Yayasan Ilomata, 2025)
This research is focused on how digital marketing affects dodol sales performance. The concept of digital marketing includes indicators such as Accessibility, Interactivity, Entertainment, Credibility, Interest, and Informative. Sales performance evaluation consists of indicators such as Sales Growth, Profit Growth, Sales Volume, Market Growth, and Customer Growth. Digital marketing plays a very important role in improving dodol sales performance. By utilizing various digital platforms, such as social media, websites, and e-commerce applications, dodol business actors can reach consumers more widely and more efficiently. This study uses a field study methodology with a quantitative perspective. The population of this study is dodol traders located in the Workshop Market, Serdang Bedagai Regency. The population of this study is 36 swordsmen and a sample of 36 traders, which were selected as a whole so that they used saturated sampling. Data were obtained from questionnaires and analyzed using simple linear regression. The results of the study show that digital marketing variables have a significant influence on the sales performance of the workshop market if considered individually. Overall, the role of digital marketing is vital in improving sales performance. With the right strategy, digital marketing can have a significant positive impact on business growth, increase product visibility, and expand market share and customer loyalty.